Targeting LAG-3 and PD-1 to Enhance T Cell Activation by Antigen-Presenting Cells - Lichtenegger, Felix S.; Rothe, Maurine; Schnorfeil, Frauke M.; Deiser, Katrin; Krupka, Christina; Augsberger, Christian; Schlüter, Miriam; Neitz, Julia; Subklewe, Marion (Frontiers in Immunology, 2018)
Immune checkpoint inhibition has been shown to successfully reactivate endogenous T cell responses directed against tumor-associated antigens, resulting in significantly prolonged overall survival in patients with various tumor entities. For malignancies with low endogenous immune responses, this approach has not shown a clear clinical benefit so far. Therapeutic vaccination, particularly dendritic cell vaccination, is a strategy to induce T cell responses. Interaction of dendritic cells and T cells is dependent on receptor-ligand interactions of various immune checkpoints. In this study, we analyzed the influence of blocking antibodies targeting PD-1, HVEM, CD244, TIM-3, and LAG-3 on the proliferation and cytokine secretion of T cells after stimulation with autologous TLR-matured dendritic cells. In this context, we found that LAG-3 blockade resulted in superior T cell activation compared to inhibition of other pathways including PD-1/PD-L1. This result was consistent across different methods to measure T cell stimulation (proliferation, IFN-γ secretion), various stimulatory antigens (viral and bacterial peptide pool, specific viral antigen, specific tumor antigen), and seen for both CD4+ and CD8+ T cells. Only under conditions with a weak antigenic stimulus, particularly when combining antigen presentation by PBMCs with low concentrations of peptides, we observed the highest T cell stimulation with dual blockade of LAG-3 and PD-1 blockade. We conclude that priming of novel immune responses can be strongly enhanced by blockade of LAG-3 or dual blockade of LAG-3 and PD-1, depending on the strength of the antigenic stimulus.